Penyederhanaan Proses Administrasi Ekspor Retur Mesin ke Altdorf di PT X dengan Analisis Makigami - Leonita Kusuma; Karina Agustin (Jurnal Titra, 2020)
Circuit-breaker industry have to return their machines to get them fixed when it comes to breakdown through the export. The process is involved with 7 departments in which several of those activities are non-value-added activities and cause wasted time for the administrastion document handling. Makigami method is use to map the flow within the process including medium, total activity, and time, in order to identify even eliminate non-value-added activity and the potential of waste. The purpose is to simplify the process into a simple and efficient process. The delivery note documents are now be managed by 2 departments with different asset ownership, which can be categorized as an unnecessary transportation. They want to integrate the person who is in charge of the delivery note documents, any miscommunication between department will subside. The result comes with reduction for 53% in the amount of total process as well as total of waste for 40% and time savings for 39%.